The Effect of Sample Volume Variation on Blood Glucose Measurements Using POCT Devices within the Context of Public Health Services - Rony Puasa; Aan Yulianingsih; Febrianti Jakaria; Nikma Nikma (Direktorat Politeknik Kesehatan Makassar, 2025)
Blood glucose testing is a crucial step in the detection and monitoring of diabetes mellitus, especially within the context of public health services. The use of Point-of-Care Testing (POCT) devices has become a practical choice due to their speed and ease of use. However, the accuracy of the test results can be influenced by various factors, one of which is the volume of the blood sample utilized. This study aims to evaluate blood glucose measurements using variations in sample volume on a POCT device. The research employed a laboratory experimental design with a within-subject approach. A total of 55 respondents participated in the study. The blood sample volume variations tested were 0.3 µl, 0.5 µl, and 0.7 µl. The measurements were carried out using the Easy Touch POCT device, and the results were compared with a standard laboratory control instrument. The study findings indicate that a blood sample volume of 0.7 µl produced glucose values most consistent with the standard laboratory results, where, based on SPSS analysis, the p-value was > 0.05 (0.137 > 0.05), indicating no significant difference between the POCT measurements and the standard laboratory instrument at this volume. In contrast, sample volumes of 0.3 µl and 0.5 µl showed significant differences compared to the reference values (p < 0.05), which could affect the accuracy of the measurements and potentially impact the accuracy of diagnosis and patient monitoring. Based on these results, it can be concluded that the volume that yields the highest accuracy for glucose testing using the Easy Touch POCT device is 0.7 µl. This study highlights the importance of standardizing blood sample volume in the use of POCT to enhance the accuracy of test results, particularly in primary healthcare settings such as community screening programs or public health centers (puskesmas).